The effect of eradicating Helicobacter pylori on idiopathic central serous chorioretinopathy patients - Dang Y; Mu Y; Zhao M; Li L; Guo Y; Zhu Y (Dove Medical Press, 2013)
Yalong Dang,1,2,* Yalin Mu,2,* Manli Zhao,2 Lin Li,3 Yaning Guo,4 Yu Zhu1,2 1Department of Ophthalmology, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People's Republic of China; 2Department of Ophthalmology and Visual Science, Yellow River Hospital of Henan University of Science and Technology, Sanmenxia City, Henan, People's Republic of China; 3Department of Ophthalmology, The First Affiliated Hospital of Henan University of Science and Technology, Luoyang City, Henan, People's Republic of China; 4Gu-Cheng Eye Hospital, Xi'an City, Shanxi, People's Republic of China *These authors contributed equally to this work Purpose: To evaluate the effect of Helicobacter pylori (H. pylori) eradication on the remission of acute idiopathic central serous chorioretinopathy (ICSCR). Study design: A prospective, randomized, placebo-controlled study of 53 participants. Main outcome measure: Twenty-seven acute ICSCR patients tested positive for H. pylori were given an eradication H. pylori therapy, and another 26 patients with the same diagnosis received matching placebo medication. All participants were tested for the following items: (1) disappearance rate of subretinal fluid (SRF); (2) best-corrected visual acuity (BCVA); and (3) central retinal sensitivity at baseline, 2 weeks, 4 weeks, 8 weeks, and 12 weeks after treatment. The difference between the two groups was analyzed by PASW statistics version 18.0. Results: At each follow-up, the disappearance rate of SRF in the active treatment group seemed slightly better than in the control group, but no statistically significant differences were observed (P > 0.05 at each follow-up). The BCVA between the two groups also did not demonstrate statistically significant differences (P > 0.05 at each follow-up). Unlike the BCVA and the disappearance rate of SRF, we compared the change in central retinal sensitivity at 12 weeks after treatment; a statistical difference was observed (P = 0.042). Conclusion: Our findings suggested that H. pylori eradication does not improve BCVA and the disappearance rate of SRF, but it could improve the central retinal sensitivity in acute ICSCR patients. We recommend that chronic ICSCR patients and more sensitive methods for H. pylori diagnosis should be involved in evaluating the effect of H. pylori eradication. Keywords: Helicobacter pylori, acute idiopathic central serous chorioretinopathy, best-corrected visual acuity, subretinal fluid, central retinal sensitivity